Synthesis, characterization and evaluation of scintillation properties of Eu3+-doped Gd2O3 obtained using PEG as precursor - Durante, Lorena P.B. (2015)
Abstract This work reports on the synthesis of Eu3+-doped Gd2O3 using PEG as an organic molecular precursor with 1, 3, 5, 7 e 10 mol% of Eu3+. TGA and DTA analysis of the precursors obtained shows that the final materials are obtained at thermal treatment above 700 °C. Based on this information all materials were obtained after heat treatment at 900, 1000 and 1100 °C during 4 h in an oven under air atmosphere. XRD analysis showed that the materials obtained after heat-treatment presents a cubic crystalline structure assigned to the Gd2O3. Crystallite size and microstrain were evaluated using the Scherrer's equation and Williansom-Hall method, respectively, as a function of heat-treated temperature and Eu3+ concentration. Raman spectroscopy also showed the formation of the Gd2O3 phase, however, the absence of bands around 117 cm-1 in the spectra with higher Eu3+ concentration indicates that the insertion of this one in the host matrix promotes the breakdown of some chemical bonds of the matrix. Intense photoluminescence emission in the visible region with maximum localized around 611 nm under excitation at 255 nm with xenon lamp and with X-ray source were observed. The emissions observed were attributed to the intraconfigurational f-f transitions of Eu3+. The lifetime values of the 5D0 excited state were between 2.84 and 2.89 ms, indicating the location of Eu3+ in crystalline systems. This result demonstrates the potential application of the materials in systems for absorption in the ultraviolet region, solar cells, devices generated images and scintillation systems.